Water uncertainty, ritual predictability and agricultural canals at Chaco Canyon, New Mexico. (22nd August 2018) - Scarborough, Vernon L.; Fladd, Samantha G.; Dunning, Nicholas P.; Plog, Stephen; Owen, Lewis A.; Carr, Christopher; Tankersley, Kenneth B.; McCool, Jon-Paul; Watson, Adam S.; Haussner, Elizabeth A.; Crowley, Brooke; Bishop, Katelyn J.; et al.
Abstract : The Pueblo population of Chaco Canyon during the Bonito Phase (AD 800–1130) employed agricultural strategies and water-management systems to enhance food cultivation in this unpredictable environment. Scepticism concerning the timing and effectiveness of this system, however, remains common. Using optically stimulated luminescence dating of sediments and LiDAR imaging, the authors located Bonito Phase canal features at the far west end of the canyon. Additional ED-XRF and strontium isotope (87Sr/86Sr) analyses confirm the diversion of waters from multiple sources during Chaco's occupation. The extent of this water-management system raises new questions about social organisation and the role of ritual in facilitating responses to environmental unpredictability.